British Abortion Law: Speaking from the Past to Govern the Future. Issue 2 (March 2016) - Sheldon, Sally
Abstract : This paper analyses the poor alignment of the aging statutory framework and modern understandings of medical best practice in the context of abortion services. With a particular focus on medical abortion, it assesses the significant challenges that the gulf between the two poses for clinicians, service providers, regulators and the courts. Law is said to be at its most effective where there is a shared regulatory community that accepts and endorses the values that underpin it. It is suggested that the example of abortion law provides a marked example of what happens when legal norms once justified by broadly shared moral understandings, concerns for patient safety and requirements of best practice are now either unsupported by or, indeed, sit in opposition to such concerns.